The evaluation of an inorganic-organic poly(carborane-siloxane-arylacetylene) hybrid resin system. (May 2023) - Monzel, William Jacob; Berglund, Kyle; Kolel-Veetil, Manoj; Simone, Davide; Gibson, Thao
The realization of aerospace vehicle technologies demanding extreme service conditions is facilitated by the development of materials with greater oxidative stability at high temperatures. Thermal performance of polymer composites can be increased by incorporating a hybrid (organic-inorganic) resin as a thermal barrier coating. One such resin system, meta -poly (carborane-siloxane-arylacetylene) ( m -PCSAA), developed by the U.S. Naval Research Laboratory, shows potential for such application and is further investigated in this work. The resin has a low viscosity (0.1 Pa s) with large processing window (2.5 h) from 100°C to 230°C. These processing characteristics are advantageous for infusion processes or the inclusion of fillers for coating applications. Curing was accomplished in two stages, corresponding to two exothermic reactions. After the first curing stage, the resin exhibits elastomeric behavior, and after the second curing stage is rigid with a high glass transition temperature (∼330°C). The materials exhibited high char yields (89%) in air at 1000°C and may be useful in space or for attritable technology. No cracks were observed during long-term service at 288°C, but significant degradation and cracking were observed after aging at 316°C. The materials exhibited high coefficients of thermal expansion; 186.9 and 168.6 μm/(m∙°C) after first and second curing stage respectively. Similar to epoxies and polyimides, the resin acquired up to 3% moisture at 70°C and 85% relative humidity.